2020
DOI: 10.1371/journal.pone.0237407
|View full text |Cite
|
Sign up to set email alerts
|

Malaria preventive practices and delivery outcomes: A cross-sectional study of parturient women in a tertiary hospital in Eastern Uganda

Abstract: Background Uganda ranks third in the number of deaths attributable to malaria and has some of the highest recorded malaria transmission rates in the general population. Malaria in Pregnancy is associated with detrimental effects for the mother and unborn baby and these effects seem to have long term effects and consequences on the life of the baby. Despite the preventive measures put in place by the World Health Organization in antenatal care, the burden of malaria in pregnancy is still high. We determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…In the present study, the prevalence of maternal peripheral malaria was 6.4%. It is comparable with a study result reported in Northwest Colombia where it was 9.1% [ 5 ], but it is higher than a study finding of 1.4% in eastern Uganda [ 18 ]. On the other hand, the present finding is lower than a study result of 15.2% in Wolkitie, Southern Ethiopia, [ 15 ] and 37.8% in Sudan [ 19 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the prevalence of maternal peripheral malaria was 6.4%. It is comparable with a study result reported in Northwest Colombia where it was 9.1% [ 5 ], but it is higher than a study finding of 1.4% in eastern Uganda [ 18 ]. On the other hand, the present finding is lower than a study result of 15.2% in Wolkitie, Southern Ethiopia, [ 15 ] and 37.8% in Sudan [ 19 ].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, it is estimated that 40 neonates per 1000 live births will experience clinical malaria during the first 7 days of life [ 10 ]. In Sub -Saharan Africa, the prevalence is estimated to be between 0 and 37% [ 4 ], while in Eastern Uganda, the prevalence of CM is reported to range from 4 to 6.1% [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The true burden of congenital malaria may be underestimated due to absence of routine screening of newborns with fever, low index of suspicion, absence of specific signs, and symptoms, coupled with the late symptom presentation. Only one-third (34%) of the affected neonates present within 72 hours of life [ 9 , 13 ]. This was the case with our patient who presented with CM within 48 hours of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations